One-loop charge-breaking minima in the two-Higgs doublet model - Ferreira, Pedro Miguel (2020)
We analyze the vacuum structure of the one-loop effective potential in the two Higgs doublet model. We find that electroweak-breaking vacua can coexist with charge breaking ones, contradicting a theorem valid at tree-level. We perform a numerical analysis of the model and supply explicit parameter values for which charge-breaking vacua can be the global minimum of the theory, and deeper than charge-preserving ones.